Obtaining and characterization of mango vinegar by the Orleans acetylation method (Research, Society and Development, 2020)
The slow process to obtain fruit vinegar is based on low speed of acetylation, with good reproducibility in the laboratory and low expense. This study aimed to produce a mango vinegar by the method of slow acetylation or Orleans method. The acetic fermentation was carried with mango fermented with an alcohol content of 7% (v. v -1) and added 100 ml of strong vinegar unpasteurized as inoculum. The fermentation occurred for 28 days, samples were removed every seven days (0, 7, 14, 21 e 28). Vinegar presented volatile acid content of 3.23 ± 0.07 %, total acidity (4.21 ± 0.11 %), pH (3.28 ± 0.03), residual ethanol (0.95 ± 0.01 %), carotenoids (12.67 ± 1.14 mg. 100mL-1) and total phenolic compounds (31.80 ± 2.00 mg catechin. 100mL-1). The acid conversion was 0.799 ± 0.01 g. g-1 and the yield Gesammte Konzentration (GK) of 64.00 ± 5.04 %. The vinegar obtained showed significant levels of total carotenoids and phenolics. It was possible to obtain sleeve vinegar by slow acetylation process, however it is necessary the development of studies regarding acetylation method in order to increase the productivity and efficiency of the process as well as to minimize evaporative losses, decrease the chances of contamination and to increase the acetic acid content in obtaining vinegar according to recommended in the current Brazilian legislation.